Kreis 48. - Kunsthalle Basel (Basel : Kunsthalle Basel, 1963)
Comment, Jean-François ; Esposito, Romolo ; Kämpf, Max ; Moilliet, Peter ; Rebholz, Johann Anton ; Schätzle, Julie ; Stöckli, Paul ; Weidmann, Hans
Kreis 48, Kunsthalle Basel, Basel, 16. März - 15. April 1963
boek